Analisis Aerodinamika Rancangan Body Kendaraan Prototype Bermesin Diesel Menggunakan ANSYS Fluent - Fadhilah Ikhsan Dinul; Randi Purnama Putra; Refdinal Refdinal; Fitrah Qalbina (Jurnal Vokasi Mekanika (VoMek), 2025)
Transportation industry is the third largest energy consumer, the focus on energy saving in vehicles and reducing exhaust emissions is major concern. Aerodynamics is one of the important subjects in vehicle engineering today. The more aerodynamic the vehicle, the lighter the engine performance, which can reduce fuel usage. This study aims to examine the effect of vehicle body design on the value of drag coefficient (Cd), lift coefficient (), and the ratio between lift coefficient and drag coefficient (/Cd). The method in this research is a numerical method that utilizes the CFD feature in the Ansys Fluent 2024 R1. The drag coefficient value with a speed of 10 m/s is 0.0155, a speed of 20 m/s is 0.0110, and a speed of 30 m/s is 0.0083. While the value of the lift coefficient with a speed of 10 m/s is obtained worth 0.0177, a speed of 20 m/s worth 0.0358, and a speed of 10 m/s worth 0.0455. Then the vehicle body design obtained the value of the /Cd ratio with a speed of 10 m/s worth 1.1419, a speed of 20 m/s worth 3.2545, and a speed of 30 m/s worth 5.4819. The conclusion this research is that the design of the vehicle body has a drag coefficient value decreasing as the speed increases and conversely the lift coefficient value increases. Based on the /Cd ratio value, it indicates that the vehicle body design is an aerodynamic design because the higher /Cd ratio, the more efficient the vehicle performance.